SOCIAL CRITICISM IN 2019 GANTI PRESIDEN LYRICS: A CRITICAL DISCOURSE ANALYSIS - Herlina, Ninin (Research And Innovation In Language Learning (RILL), 2019)
This study aimed to determine the dimension of text. The use of vocabulary and grammar is not independent, there are micro, meso, and macro context that connect to the text in which makes certain practices and objectives a writer. This research aimed to clarify the meaning of the social criticism lyrics “2019 Ganti Presiden” and struggle for social values. This research used qualitative approach by analysis of discourse methods and critical paradigms. The result showed that social criticism of the song “2019 Ganti Presiden” represented awarness and an invitation to unlimited solidarity to learn about humanity, justice, help the lower classes such as laborers and hawkers. The lyrics of “2019 Ganti Presiden” also represented marginalization and personal opinion. “2019 Ganti Presiden”  was produced in 2018 according to the typical situation of Indonesia that regarding the economy, political conditions in Indonesia which resulted in unemployment and corruption. The lyrics of the song "2019 Ganti Presiden" are spread massively and become a new political discourse in Indonesian history